Applied research note: Heating system and feed additive effects on foot pad quality, broiler performance, and immune status - V.E. Ayres; T.P. Boltz; K.M. Bowen; S. Grushecky; J. Wang; J.S. Moritz (Journal of Applied Poultry Research)
Summary: Radiant propane brooders are commonly used to heat poultry houses in the United States. However, brooders combust within the house, releasing moisture into the grow-out environment. The objectives of this study were to investigate the effects of two feed additives (antibiotic and muramidase) provided to broilers reared using two heating systems (external combustion wood boiler heat exchanger or radiant propane brooders), on broiler performance, foot pad quality, and immune status. Two identical experiments were completed, using two identical rooms heated with either radiant propane brooders or a wood boiler heat exchanger. 1,472 Ross-308-AP straight-run broiler chicks were utilized for each experiment, for 35d. Each room contained 32 floor pens. One of four dietary treatments (positive control (PC), negative control (NC) (15 % reduction in digestible amino acids), NC+antibiotic, NC+muramidase) were randomly assigned to each pen within a block. A block consisted of four adjacent floor pens; eight blocks were utilized per room per experiment. Use of a wood boiler heat exchanger reduced d21 litter moisture (P = 0.1013), d23 serum interleukin-6 (P < 0.0001), and d35 foot pad scores (FPS) (P = 0.0112), relative to radiant propane brooders. Diet influenced 0-35d live weight gain (LWG) and FCR. The PC had the highest LWG and lowest FCR, NC had the lowest LWG and highest FCR, with antibiotic and muramidase being intermediate (P < 0.05). Birds fed the PC had higher d35 litter moisture and FPS (P < 0.05). Heating system type did not affect overall performance (P > 0.05). The wood boiler heat exchanger and both tested feed additives had positive influences on broiler production.